Analysis of The influence of Attractions, Amenities, Accessibility, and Ancillary on Service Satisfaction for Visitors of Coastal Tourism Objects Manohara Pidie Jaya District - Hamidah, Cut; Novalita, Rahmi; Fitrah, Hariki (Sumatra Journal of Disaster, Geography and Geography Education, 2024)
This research aims to describe; 1) the influence of attractions on visitor service satisfaction at the Manohara Beach tourist attraction, 2) the influence of accessibility on service satisfaction for visitors at the Manohara Beach tourist attraction, 3) the influence of amenities on service satisfaction for visitors at the Manohara Beach tourist attraction, 4) the influence of Ancilary on satisfaction services for visitors at the Manohara Beach tourist attraction, 5) the influence of attraction, accessibility, amenities and ancillary together on service satisfaction for visitors at the Manohara Beach tourist attraction. This type of research is quantitative research. The research sample was 100 visitors to the Manohara beach tourist attraction. The sampling technique uses incidental sampling. Data collection techniques use questionnaires. The data analysis technique uses multiple linear regression analysis tests. The results of the research show that: 1) attractions partially have a positive and significant influence on tourist service satisfaction, 2) partial accessibility does not have a positive and significant influence on tourist service satisfaction, 3) partial amenities have a positive but not significant influence on service satisfaction tourists, 4) the ancillary partially has a positive and significant influence on tourist service satisfaction, 5) Attractions, Accessibility, Amenities and Ancillary have a positive and significant influence on the service satisfaction of tourists visiting the Manohara Beach tourist attraction, Pidie Jaya Regency.